2018
DOI: 10.7717/peerj.4671
|View full text |Cite
|
Sign up to set email alerts
|

Fine grained compositional analysis of Port Everglades Inlet microbiome using high throughput DNA sequencing

Abstract: BackgroundSimilar to natural rivers, manmade inlets connect inland runoff to the ocean. Port Everglades Inlet (PEI) is a busy cargo and cruise ship port in South Florida, which can act as a source of pollution to surrounding beaches and offshore coral reefs. Understanding the composition and fluctuations of bacterioplankton communities (“microbiomes”) in major port inlets is important due to potential impacts on surrounding environments. We hypothesize seasonal microbial fluctuations, which were profiled by hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…All 240 sediment samples were processed for DNA analyses. Preparation of DNA samples from sediment and water acquired for high-throughput 16S rRNA gene sequencing were conducted as described in detail in previous studies ( Campbell et al, 2015 ; O’Connell et al, 2018 ; Easson & Lopez, 2019 ). Briefly, after pelleting 1–2 grams of sediment, genomic DNA was extracted using the DNeasy PowerLyzer Powersoil kit (12855; Qiagen, Hilden, Germany) following standard protocols.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All 240 sediment samples were processed for DNA analyses. Preparation of DNA samples from sediment and water acquired for high-throughput 16S rRNA gene sequencing were conducted as described in detail in previous studies ( Campbell et al, 2015 ; O’Connell et al, 2018 ; Easson & Lopez, 2019 ). Briefly, after pelleting 1–2 grams of sediment, genomic DNA was extracted using the DNeasy PowerLyzer Powersoil kit (12855; Qiagen, Hilden, Germany) following standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…These primers have been selected because they can amplify and provide the most comprehensive diversity of both Bacteria and Archaea. The resulting 16S rRNA gene libraries were purified with AMPure beads and prepared for sequencing on an Illumina MiSeq following the manufacturer’s protocol for library preparation and Miseq Reagent Kit v3 for 250 bp paired end reads and with custom indices needed for protocol outlined by the Earth Microbiome Project ( Thompson et al, 2017 ; O’Connell et al, 2018 ; Easson & Lopez, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 16S rRNA gene fragment was the target for bacterial identification via high throughput DNA sequencing (O'Connell et al, 2018;Easson and Lopez, 2019). Samples were prepared for sequencing following the 16S Illumina Amplicon Protocol per the Earth Microbiome Project (Kuczynski et al, 2011;Thompson et al, 2017).…”
Section: Illumina High-throughput 16s Sequencing and Analysismentioning
confidence: 99%
“…Hence, any influence that sea-level (including tides) had on these microbiomes was more likely due to low-frequency variability in currents and/or transports forced by sea-level gradients, rather than to the sea-level variations themselves. In particular, low-frequency variability from both wind setup and tide can drive cross-shelf transport (Castelao et al, 2010; Lee & Smith, 2002; Leichter et al, 1996), affecting microbial connectivity (Säwström et al, 2016), flushing times (Castelao et al, 2010), and the availability of prey and nutrient inputs (Leichter, Stewart & Miller, 2003; Monismith et al, 2010; O’Connell et al, 2018). Such effects may serve to reduce microbial alpha-diversity on reefs (O’Connell et al, 2018) and may explain the correlations we observed.…”
Section: Discussionmentioning
confidence: 99%